Competency Map of the Academic Chair - David A Line; Stephen F Pyle (Academic Chairpersons Conference Proceedings, 2019)
The growth of Competency Based Education (CBE) has led to the strengthening of programs in many fields. This trend has introduced new opportunities to assess student progress and program outcomes. Competency Based Chairing uses these same tools to develop stronger chairs. This interactive session explores ways of getting the most out of professional competencies in our growth as chairs.
Keywords: Competency Based Chairing; Professional Evaluation